Coping Mechanisms of Hospitality Industry Workers in a Tourism Destina-tion during the Covid-19 Pandemic - Danay, Bezaleel Joy Murchante; Danay, Zephaniah Dela Cruz; Escarilla, Cherry Colesio; Maming, Jimmy Bernabe (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The Covid-19 pandemic brought massive devastations to the different levels of society. The World Travel and Tourism Council had recently warned that Covid-19 pandemic could lead to a cut of 50 million jobs worldwide in the travel and tourism industry. A study conducted by Oxford reveals that Asia will be vilest to be affected by the pandemic and it would take time to recover its economy (Dogra, 2020). This means a wider and greater impacts to the different industries including the tourism sector. The study aims to explore the coping mechanisms of hospitality industry workers in Boracay Island during the Covid-19 pandemic particularly on their experiences during the Covid-19 pandemic and to determine the coping mechanisms of hospitality workers in Boracay Island being affected by the pandemic. The case study method through a qualitative analysis using Robert Yin's approach in the data analysis procedure to explore the data from the experiences of the key informants from the hospitality industry was used. Themes came out from the construct of the key informants like (1) hospitality industry workers experienced mental health, social, and economic issues, (2) The pandemic opens new opportunities and ways to cope with its effects. The output of this research is the proposed Danay, Danay, Escarilla, and Maming Model for Coping Mechanisms of Hospitality Industry workers during the Covid-19 Pandemic.